The determinants and engagement patterns of chaperones and chauffeurs by Australian doctors in after-hours house-call services - Ifediora,Chris Onyebuchi (PeerJ, 2017)
Objectives The use of escorts (chauffeurs and chaperones) while on duty in after-hours-house-call (AHHC) is one key protective option available to doctors in the service, and has been linked to low burnout and increased satisfaction in AHHC. This study aims to explore the patterns of engagement of escorts in Australian AHHC. Method This is a questionnaire-based, electronic survey of all 300 doctors involved in AHHC through the National Home Doctor Service (NHDS), Australia’s largest providers of the service. The survey explored the doctor’s experiences over the 12-month period from October 2013 to September 2014. Results This survey received a total of 168 valid responses, giving a response rate of 56%. Nearly 61% of the doctors involved in AHHC engaged escorts (chauffeurs and chaperones). Of those doctors that engage chauffeurs, three-quarters do so “all or most times”, while only one-quarter engaged chaperones to the same degree of frequency. Hiring escorts is very popular among Brisbane (91.7%) and Sydney-based (88.2%) practitioners, but is unpopular in the City of Gold Coast (26.1%). There were moderate patronages in Adelaide (52.9%) and Melbourne Area (46.4%). Compared to males, females were less likely to drive themselves without escorts (OR 0.20; P < 0.01; CI [0.07–0.57]), but more likely to engage chauffeurs (OR 5.87; P = 0.03; CI [1.16–29.77]). Practitioners who were apprehensive were three times more likely to either engage escorts as chauffeurs (OR 3.10; P = 0.04; CI [1.05–9.15]) or as an accompanying chaperone if they self-drive (OR 3.03; P = 0.02; CI [1.16–7.89]). Conclusion More needs to be done to increase the engagement of escorts by doctors involved in the Australian AHHC, particularly given their proven benefits in the service. Future studies may be needed to fully explore the real reasons behind the significant associations identified in this study.
Keywords: Chauffeur; Chaperone; Doctors; General practice; After-hours; Family physicians; General practice; after-hours; Protection; Home visits; Family physicians.